Plasma DNMT1 Activity for Assessing Tumor Burden and Predicting Neoadjuvant Therapy Response in Breast Cancer - Yingran Wang; Guozhi Zhang; Zhizhao Zhang; Mengsi Zhang; Jiao Chen; Ke Wang; Lu Liu; Jing Bao; Ming Chen; Xiaowei Qi; Mingxuan Gao (Advanced Science)
Abstract DNA methylation is mediated by DNA methyltransferases (DNMTs), and the stability of their activity is essential for cellular fate. DNMT1 is considered one of the most promising targets for research. However, current detection techniques are limited in accurately quantifying its activity in peripheral blood. Here, a reaction system is developed known as DNMT1 Identification by Variable Activity (DIVA) for the highly sensitive detection of DNMT1 activity in the peripheral blood of breast cancer patients. DIVA can detect DNMT1 at levels as low as 10−7 U mL−1, with minimal time and cost. This method is applied to analyze 271 clinical samples, successfully evaluating tumor burden in patients staged I‐IV. Finally, this method is utilized to assess the prognosis of 22 patients undergoing neoadjuvant therapy, demonstrating good consistency with ultrasound imaging results. It is believed that DIVA could serve as an effective auxiliary technique for both the early detection of breast cancer and evaluation of neoadjuvant therapy.